Hydrophilic and lubricated corneal contact lens
By using an interpenetrating polymer network structure formed by partially hydrolyzed polyvinyl alcohol and polyvinylpyrrolidone on the contact lens, the problem of high surface friction of the contact lens is solved, achieving long-term lubrication effects and reducing production costs.
Patent Information
- Application Number
- CN202410435296.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-02-22
- Filing Date
- 2024-04-11
- Publication Date
- 2025-01-24
AI Technical Summary
When wearing existing soft corneal contact lenses, due to the large surface friction, the user feels that something is in the eyes. The traditional polyacrylic acid (PAA) coating is easily affected by the pH value of the tear, resulting in discomfort in wearing.
The interoperable polymer network structure containing parts of hydrolysis polyethylene (PVA) and polyethylene pyrirol (PVP) is used as the shell layer. It forms a stable hydrogen bond and cross -linking response through the high temperature and high pressure sterilization process to improve the lubrication of the lens surface And stability.
It effectively increases the lubrication of the contact lens surface, improves wearing comfort, and the effect can be maintained for a long time, while reducing production costs.
Smart Images

Figure BDA0004787020100000091 
Figure BDA0004787020100000101 
Figure BDA0004787020100000102
Abstract
Description
Technical Field
[0001] The invention relates to a corneal contact lens, in particular to a hydrophilic and lubricating corneal contact lens. Background Art
[0002] Soft contact lens materials were introduced in the 1960s. The softness of the material solved the discomfort often experienced by hard contact lenses (RGP lenses) when worn. Users who were not used to hard contact lenses could switch to soft contact lenses. Therefore, soft contact lenses have become the main choice for today's contact lens users.
[0003] Although soft contact lenses are much softer and more comfortable than hard contact lenses, many users still complain that they feel something in their eyes when wearing soft contact lenses, which has prompted these users to give up using contact lenses. The main reason for the above problem is that the surface of the contact lens has friction, so when blinking, the lens moves on the eyeball and rubs the eyeball, causing the user to feel something in the eye. Therefore, increasing the lubricity of the lens surface can solve the above problem.
[0004] There are many studies on coating the lens surface with polyacrylic acid (PAA) to achieve the effect of surface lubrication. However, PAA is an anionic polymer, which tends to carry a negative charge. Its properties are easily affected by the pH value in tears, which may cause irritation when worn. Subsequent studies have revealed the use of cationic polymers to neutralize the electrical properties of PAA in order to improve the stability of the above technology, but this method requires a lot of control costs in the process, and the product cannot stably maintain the lubrication effect for long-term wear. Summary of the invention
[0005] In view of the above problems and technological development, the present invention proposes a method that can effectively increase the lubricity of the surface of a corneal contact lens, and the effect can be maintained for a long time, while having a cost-competitive technical solution.
[0006] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. In general, the nomenclature and laboratory procedures used herein are well-known and commonly used in the art. Conventional methods are used for these processes, such as those provided in this area and various general references. When a term is provided in the singular, the inventor also contemplates the plural form of the term. The nomenclature used herein and the laboratory procedures described below are well-known and commonly used in the art. As used in the full text of this disclosure, unless otherwise indicated, the following terms should be understood to have the following meanings.
[0007] Dry lens: refers to the lens that has completed curing but has not yet been hydrated during the production of corneal contact lenses.
[0008] Wet lens: refers to the lens that has completed hydration during the production of corneal contact lenses.
[0009] Core lens body: refers to the part of the lens formed by curing the contact lens formulation. The core lens body can be a dry lens or a wet lens. Some of the embodiments of the present invention do not have a shell layer.
[0010] Shell layer: refers to the layer formed on the surface of the lens core body after the lens core body has been formed and then solidified through other processes. However, it is not the structure of the original lens core body. At the same time, by forming a stable structure similar to an interpenetrating polymer network structure, the shell layer can stably exist on the surface of the lens core body.
[0011] Interpenetrating polymer networks (IPNs): Generally, the interpenetrating polymer network structure is defined as a polymer network that includes two or more polymers, at least one of which is a cross-linked polymer network structure, and at least two or more polymers are partially interlaced on the polymer scale but do not form covalent bonds with each other. For example, polymer A itself is a cross-linked polymer network structure, and polymer B is partially interlaced with polymer A, but polymer A and polymer B do not form covalent bonds, then polymer A and polymer B can be said to form an interpenetrating polymer network structure. Considering the complexity of the polymer and chemical fields, the interpenetrating polymer network structure used in the present invention refers to objects, and different polymers are allowed to covalently bond in the process and results of forming the interpenetrating polymer network structure. For example, in the case disclosed in the present invention, it is not excluded that a small amount (less than 0.1wt%) of the first polymer is covalently bonded with the polymer of the lens core body. For the convenience of expression, the inventor still uses the interpenetrating polymer network structure to describe the partially interlaced polymer network formed by the first polymer and the polymer of the lens core body on the surface of the lens core body. The polymer structure formed by the entanglement of the first polymer and the second polymer in the outer shell layer is called a stable structure similar to an interpenetrating polymer network structure, because in this polymer structure, the polymeric chain of the first polymer itself does not have obvious crosslinking, and the second polymer itself does not have obvious crosslinking. It is just that there are strong hydrogen bonds between the polymer chains of the first polymer, and there are also strong hydrogen bonds between the polymer chains of the first polymer and the second polymer, thus forming a stable structure similar to an interpenetrating polymer network structure. Therefore, the present invention does not directly use the interpenetrating polymer network structure to describe the network structure formed by the first polymer and the second polymer in the outer shell layer, so as to be as close as possible to the general theoretical definition.
[0012] Semi-IPN: Generally defined in theory, at least one polymer in an IPN is a linear polymer. The IPN structure of the present invention may include a semi-IPN structure.
[0013] Simultaneously interpenetrating polymer network (Simultaneous-IPNs, SINs): Generally defined in theory, it specifically refers to the formation of an interpenetrating polymer network structure that originates from the formation of two or more polymer constituent units when each of them undergoes a polymerization reaction. For example, an interpenetrating polymer network structure is composed of polymer A and polymer B, where polymer A is formed by a polymerization reaction of monomer a, and polymer B is formed by a polymerization reaction of monomer b. If monomer a and monomer b are mixed and the mixture is subjected to a polymerization reaction, the interpenetrating polymer network structure of polymer A and polymer B that is finally formed may be a simultaneous interpenetrating polymer network structure. The interpenetrating polymer network structure involved in the present invention, for example, does not include a simultaneous interpenetrating polymer network structure.
[0014] The present invention provides a corneal contact lens, comprising a core lens body and a shell layer, wherein the shell layer covers the core lens body, wherein the shell layer comprises at least two polymers: a first polymer and a second polymer.
[0015] The first polymer used in the present invention is a polymer containing a polyvinyl alcohol (Polyvinyl alcohol) structure. The first polymer can be polyvinyl alcohol, or a copolymer of polyvinyl alcohol and polyvinyl acetate (PVA-PVAccopolymer), or a mixture of the two. Among them, the first polymer can be cross-linkable or non-cross-linkable. The copolymer of polyvinyl alcohol and polyvinyl acetate can be a block copolymer, an alternative copolymer, a random copolymer, or a graft copolymer. Polyvinyl alcohol can be cross-linkable or non-cross-linkable. Polyvinyl alcohol can be fully hydrolyzed (fully hydrolyzed), i.e. fully hydrolyzed polyvinyl alcohol (fully hydrolyzed PVA), or partially hydrolyzed (partially hydrolyzed), i.e. partially hydrolyzed polyvinyl alcohol (partially hydrolyzed PVA). Partially hydrolyzed polyvinyl alcohol is preferred. In terms of classification, partially hydrolyzed polyvinyl alcohol can also be understood as a copolymer of polyvinyl alcohol and polyvinyl acetate (PVA-PVAc copolymer), because its polymer chain segments contain both vinyl alcohol and vinyl acetate units. Further, fully hydrolyzed polyvinyl alcohol is polyvinyl alcohol whose composition is 100% vinyl alcohol units; and partially hydrolyzed polyvinyl alcohol, such as partially hydrolyzed polyvinyl alcohol with a hydrolysis degree of 80%, means that it contains 80% vinyl alcohol units and 20% unhydrolyzed vinyl acetate units. In the vocabulary expression of the present invention, partially hydrolyzed polyvinyl alcohol and the copolymer of polyvinyl alcohol and polyvinyl acetate can refer to the same object, and the two terms can be used interchangeably.
[0016] In the present invention, the first polymer is preferably partially hydrolyzed polyvinyl alcohol. The preferred range of the degree of hydrolysis of the partially hydrolyzed polyvinyl alcohol is 70%-99%, the more preferred range is 80%-98%, and the more preferred range is 88%-95%. The present invention has found that an appropriate degree of hydrolysis of polyvinyl alcohol can increase the stability of the interpenetrating polymer network structure formed between the polyvinyl alcohol and the polymer on the surface of the lens core body, and can also increase the stability of the interpenetrating polymer network structure formed between the first polymer and the second polymer in the outer shell layer. The reason why the partially hydrolyzed polyvinyl alcohol can be better than the fully hydrolyzed polyvinyl alcohol is that the fully hydrolyzed polyvinyl alcohol has a stronger intramolecular hydrogen bond, which easily leads to the fully hydrolyzed polyvinyl alcohol being relatively difficult to enter the surface structure of the lens core body (polymer) and not easy to form an interpenetrating polymer network structure with the lens core body (polymer); similarly, the fully hydrolyzed polyvinyl alcohol is less likely to form intermolecular hydrogen bonds with the second polymer containing polyvinyl pyrrolidone because of the stronger intramolecular hydrogen bonds. Therefore, compared with partially hydrolyzed polyvinyl alcohol, fully hydrolyzed polyvinyl alcohol is less likely to form a similar interpenetrating polymer network structure with the second polymer.
[0017] The molecular weight (Mw) of the first polymer is preferably in the range of 5,000-300,000 Da, more preferably in the range of 10,000-200,000 Da, more preferably in the range of 15,000-150,000 Da, and even more preferably in the range of 25,000-100,000 Da.
[0018] The second polymer used in the present invention is a polymer containing a polyvinyl pyrrolidone structure. The second polymer can be polyvinyl pyrrolidone, or a copolymer containing polyvinyl pyrrolidone, or a mixture of the two. The second polymer can be cross-linkable or non-cross-linkable. The copolymer containing polyvinyl pyrrolidone can be a copolymer of vinyl pyrrolidone and dimethylaminoethyl methacrylate (Poly (vinylpyrrolidone)-co-(dimethylaminoethylmethacrylate), and specific examples can be products sold by Ashland Inc. such as Copolymer 845, Copolymer 937 or Copolymer 958. The molecular weight of the copolymer of vinyl pyrrolidone and dimethylaminoethyl methacrylate is, for example, greater than or equal to 100,000 Da.
[0019] The molecular weight (Mw) of the second polymer is preferably in the range of 8,000Da or more, more preferably in the range of 100,000Da or more, more preferably in the range of 160,000Da or more, and more preferably in the range of 360,000Da or more. The above-mentioned molecular weight range of the second polymer can form a more effective shell layer. When the molecular weight of the second polymer is not large enough, it is difficult to form an effective shell layer with the first polymer. It is speculated that when the molecular weight of the second polymer is not large enough, although it can still form a similar interpenetrating polymer network structure with the first polymer, the second polymer will be easy to move in the structure due to its small molecular weight, resulting in insufficient stability of the shell layer.
[0020] At the junction of the lens core body and the outer shell, the first polymer and the polymer structure of the lens core body form an interpenetrating polymer network structure. In most areas of the outer shell, the first polymer and the second polymer form a stable structure similar to the interpenetrating polymer network structure.
[0021] At the junction of the lens core body and the outer shell layer, the first polymer forms an interpenetrating polymer network structure with the polymer structure of the lens core body. In the interpenetrating polymer network structure, a part of the first polymer is a freely movable polymer, and another part of the first polymer forms a stable bonding, which stabilizes the above-mentioned interpenetrating polymer network structure. The formation of the bonding mainly comes from the high temperature and high pressure in the autoclave process of the corneal contact lens, which causes stable hydrogen bonds between polyvinyl alcohols. Therefore, the part of the outer shell layer in contact with the lens core body is mainly composed of the first polymer, and the part of the outer shell layer away from the lens core body is mainly composed of the second polymer. In most areas of the outer shell layer, a stable structure similar to the interpenetrating polymer network structure is formed between the first polymer and the second polymer; wherein, a part of the first polymer is a freely movable polymer, a part of the second polymer is a freely movable polymer, and a part of the first polymer forms a stable bonding, which stabilizes the similar interpenetrating polymer network structure. The formation of this bond mainly comes from the stable hydrogen bond between polyvinyl alcohol and polyvinyl alcohol during the sterilization process of the corneal contact lens. At the same time, polyvinyl alcohol can also form stable hydrogen bonds with polyvinyl pyrrolidone, mainly from the hydroxyl group on polyvinyl alcohol and the oxygen atom on polyvinyl pyrrolidone. Therefore, the structure of the entire outer shell layer can be relatively stable, maintaining the comfort of the user during the wearing process.
[0022] Further explanation: controlling the proportion of vinyl acetate in the first polymer (i.e., the degree of hydrolysis of partially hydrolyzed polyvinyl alcohol) can significantly affect the effect of forming the outer shell. The polyvinyl alcohol structure itself has strong crystallinity. If the crystallinity of the first polymer is too strong, the first polymer cannot effectively enter the surface structure of the lens core body before forming the outer shell, resulting in the first polymer being unable to form a semi-interpenetrating polymer network structure with the surface structure of the lens core body, and naturally unable to form a relatively stable interpenetrating polymer network structure in the subsequent sterilization process. At the same time, if the crystallinity of the first polymer is too strong, the oxygen atom on the polyvinyl pyrrolidone in the second polymer is difficult to form a hydrogen bond with the hydroxyl group of the polyvinyl alcohol in the first polymer, so it is not easy for the first polymer and the second polymer to generate sufficient entanglement, which will also affect the effect of the first polymer and the second polymer forming a similar interpenetrating polymer network structure, and further affect the stability of the outer shell. At the same time, part of the vinyl acetate in the first polymer can react with part of the vinyl alcohol during sterilization to form an effect similar to a cross-linking reaction, which can further stabilize the structure of the outer shell layer and help the outer shell layer fix and cover the core body of the lens.
[0023] One of the important reasons for the formation of the stable outer shell mentioned in the present invention is that the first polymer can form an interpenetrating polymer network structure with the lens core body, and the first polymer can also form an interpenetrating polymer network structure with the second polymer. Among them, the important reason for the formation of a stable interpenetrating polymer network structure is the sterilization process. Due to the high temperature and high pressure during sterilization, the polyvinyl alcohol in the first polymer generates a stable hydrogen bond. At the same time, part of the vinyl acetate in the first polymer can react with part of the vinyl alcohol during sterilization to form a similar cross-linking reaction. This makes the surface structure of the original first polymer and the lens core body change from the originally formed semi-interpenetrating polymer network structure to a more stable interpenetrating polymer network structure. Similarly, the first polymer and the second polymer in the outer shell layer are originally simply physically adsorbed or have a small amount of entanglement. After the high temperature and high pressure during sterilization, hydrogen bonds and similar cross-linking reactions are formed between the first polymers, and the hydrogen bonds between the first polymer and the second polymer are also strengthened, further strengthening the strength of the entanglement. Therefore, the sterilization process not only helps the outer shell layer to stably cover the lens core body, but also helps to strengthen the stability of the outer shell layer itself.
[0024] The first polymer used in the present invention may not contain a cationic polymer segment, and may not contain an anionic polymer segment.
[0025] The first polymer used in the present invention may contain a positively charged polymer segment, but the positively charged polymer segment should not inhibit the formation of an interpenetrating polymer network structure between the first polymer and the polymer of the lens core body, nor should it inhibit the formation of a stable entanglement between the first polymer and the second polymer. Similarly, the first polymer used in the present invention may contain a negatively charged polymer segment, but the negatively charged polymer segment should not inhibit the formation of an interpenetrating polymer network structure between the first polymer and the polymer of the lens core body, nor should it inhibit the formation of a stable entanglement between the first polymer and the second polymer.
[0026] The second polymer used in the present invention may not contain a cationic polymer segment, and may not contain an anionic polymer segment.
[0027] The second polymer used in the present invention may contain a positively charged polymer segment, but the positively charged polymer segment should not inhibit the formation of an interpenetrating polymer network structure between the first polymer and the polymer of the lens core body, nor should it inhibit the formation of a stable entanglement between the second polymer and the first polymer. Similarly, the second polymer used in the present invention may contain a negatively charged polymer segment, but the negatively charged polymer segment should not inhibit the formation of an interpenetrating polymer network structure between the first polymer and the polymer of the lens core body, nor should it inhibit the formation of a stable entanglement between the second polymer and the first polymer.
[0028] In order to facilitate readers' understanding, we try our best to use detailed theoretical explanations on the structural relationship and principle between the first polymer and the lens core body, as well as the structural relationship and principle between the first polymer and the second polymer. However, the theoretical explanations should not be extended and further interpreted as limiting the scope of the patent rights applied for by the present invention.
[0029] As shown in the embodiments, the contact lens provided by the present invention may be mainly composed of HEMA (2-hydroxyethyl methacrylate), that is, HEMA accounts for more than 85%, or HEMA accounts for more than 90%, or HEMA accounts for more than 95%. The calculation of the composition and proportion described herein does not include a diluent. This type of contact lens is generally also called a hydrogel contact lens.
[0030] As shown in the embodiments, the corneal contact lens provided by the present invention may have a core body of a corneal contact lens containing a silicone containing component. The silicone containing component may be a silicone monomer or a silicone macromer, and may also contain a silicone crosslinker. This type of corneal contact lens is generally also called a silicone hydrogel contact lens.
[0031] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the following specifically cites a preferred embodiment and describes it in detail with the accompanying drawings as follows. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 FIG. 4 is a cross-sectional schematic diagram of a corneal contact lens according to an embodiment of the present invention.
[0033] Figure 2 for Figure 1 Enlarged schematic diagram of circle A in the middle. DETAILED DESCRIPTION
[0034] Reference will now be made in detail to embodiments of the present invention, and one or more examples thereof will be described. Each embodiment is provided to explain the present invention, not to limit the present invention. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present invention without departing from the scope or spirit of the present invention. For example, features disclosed or described as part of one embodiment may be used in another embodiment to produce another new embodiment. Therefore, the present invention is intended to encompass such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features, and directions of the present invention are disclosed in or apparent from the following detailed description. It will be appreciated by those skilled in the art that the present discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present invention.
[0035] Figure 1 FIG. 4 is a cross-sectional schematic diagram of a corneal contact lens according to an embodiment of the present invention. Figure 2 for Figure 1 Enlarged diagram of circle A. Please refer to Figure 1 and Figure 2 In one embodiment of the present invention, a corneal contact lens 100 comprises a lens core body 110 and a shell layer 120, wherein the shell layer 120 covers the lens core body 110; wherein the shell layer 120 comprises a first polymer 121 and a second polymer 122, wherein the first polymer 121 comprises polyvinyl alcohol, and the second polymer 122 comprises polyvinyl pyrrolidone. For example, the first polymer 121 covers the lens core body 110, and the second polymer 122 covers the first polymer 121.
[0036] Lens formula ingredient code and compound description:
[0037]
[0038] Implementation sample 1-1 (EX1-1): Preparation of Hydrogel-1 dry lens, lens formula see Table 1. The process from lens formula preparation to lens dry lens is a well-known technology in the art, and the casting method can be selected for preparation. The curing method of corneal contact lenses can be selected from light curing or thermal curing, and light curing is selected in this embodiment. The lens dry sheet is hydrated with hot water at 70±5 degrees Celsius (using reverse osmosis water (RO water)) for 60 minutes, and the residual monomers, cross-linking agents, initiators, and diluents in the lens dry sheet after the curing reaction are washed to obtain a lens wet sheet. After obtaining the lens wet sheet, the lens wet sheet is immersed in an aqueous solution containing 0.2g / L of PVA-PVAc copolymer for 120 minutes. The purpose of the immersion process is to allow the PVA-PVAc copolymer to enter the surface layer of the lens core body through mass transfer. The PVA-PVAc copolymer used here is numbered PVA-PVAc-1, which is a PVA-PVAc copolymer with a molecular weight of 31,000 Da and a PVA ratio of 88%, that is, a partially hydrolyzed polyvinyl alcohol with a hydrolysis degree of 88%. After completing the above steps, the wet lens is removed from the PVA-PVAc copolymer aqueous solution and placed in a polypropylene (pp) cup. Buffer-1 is dripped into the pp cup. The buffer liquid level must be higher than the wet lens to ensure that all the buffer covers the wet lens. After completion, the aluminum foil and the PP cup are sealed by heat sealing, and then sent to the autoclave for high pressure sterilization (autoclave). The sterilization conditions are to continuously raise the temperature to 122 degrees Celsius, maintain 122 degrees Celsius, 2 atmospheres and continue for 30 minutes. In this way, a corneal contact lens with HEMA as the main component and a water content of about 38% is obtained, and the outer shell layer is mainly composed of PVA-PVAc copolymer and PVP, and the PVA-PVAc copolymer is used to connect the lens core body and PVP. About 12 hours (including the sterilization process) from the beginning of the wet lens contact with the buffer solution, the aluminum foil is torn off, the corneal contact lens is taken out, and placed in a standard buffer solution (Standard buffer) for balance. One corneal contact lens uses 10 ml of standard buffer salt, and the buffer is replaced every 1 hour. Repeat 3 times, and then the surface lubricity of the corneal contact lens is scored. The formula ratio (also referred to as "ratio") of Buffer-1 and Standard buffer is recorded in Table 2.
[0039] Table 1
[0040]
[0041] Note: The diluents in Table 1 (including Glycerin, 1-Hexanol, DEGBE) are not included in the calculation of the total lens formula (SUM). Instead, they are added additionally based on 100% of the SUM as the denominator. For example: If the Hydrogel-1 formula contains HEMA98.5g, MAA 0.1g, EGDMA 1.0g, and Irgracure819 0.4g, and the total weight is 100g, then Glycerin 15.0g is added as a diluent.
[0042] Table 2
[0043]
[0044]
[0045] Note: The unit of values in Table 2 is gram weight (g). PVP360K is PVP with a molecular weight of 360,000Da, PVP8K is PVP with a molecular weight of 8,000Da, PVA-PVAc-1 is a PVA-PVAc copolymer with a molecular weight of 31,000Da and PVA accounting for 88% of the total, PVA-PVAc-2 is a PVA-PVAc copolymer with a molecular weight of 205,000Da and PVA accounting for 88% of the total, and PVA-PVAc-3 is a PVA-PVAc copolymer with a molecular weight of 27,000Da and PVA accounting for 98% of the total.
[0046] Implementation sample 1-2 (EX1-2): Follow the method of implementation sample 1-1, but after completing the heat sealing to seal the aluminum foil and the PP cup, do not send it into the autoclave for high pressure sterilization (autoclave), just let the wet lens soak in Buffer-1 in the PP cup with the aluminum foil sealed by heat. After about 12 hours (including the sterilization process) from the time the wet lens contacts the buffer, tear off the aluminum foil, take out the corneal contact lens, and put it in the standard buffer solution (Standard buffer) for balance. Use 10ml of standard buffer salt for one corneal contact lens, and change the buffer every 1 hour, repeat 3 times, and then measure the surface lubricity of the corneal contact lens.
[0047] Implementation sample 2-1 (EX2-1): Preparation of Hydrogel-2 lens dry film, lens formula is shown in Table 1. The process from lens formula preparation to lens dry film is a well-known technology in the art, and the casting method can be selected for preparation. The curing method of corneal contact lens can be selected from light curing or heat curing. In this embodiment, light curing is selected. The lens dry film is soaked in an aqueous solution containing 0.5wt% sodium carbonate for 20 minutes, the purpose is to allow the MAA in the lens dry film to be quickly ionized, so that the lens dry film can expand to increase the cleaning efficiency, and then hydrated with RO water at room temperature (20-30 degrees Celsius) for 40 minutes, and the residual monomers, crosslinking agents, initiators, and diluents in the lens dry film after the curing reaction are washed to obtain a lens wet film. After obtaining the lens wet film, the lens wet film is immersed in an aqueous solution containing 0.2g / L PVA-PVAc copolymer for 120 minutes. The purpose of this soaking process is to allow PVA-PVAccopolymer to enter the surface layer of the lens core body through mass transfer. The PVA-PVAccopolymer used here is numbered PVA-PVAc-1, which is a PVA-PVAccopolymer with a molecular weight of 31,000 Da and a PVA ratio of 88%, that is, a partially hydrolyzed polyvinyl alcohol with a hydrolysis degree of 88%. After completing the above steps, the wet lens is removed from the PVA-PVAc copolymer aqueous solution and placed in a pp cup. Buffer-1 is dripped into the pp cup. The buffer liquid level must be higher than the wet lens to ensure that all the buffer covers the wet lens. After completion, the aluminum foil is sealed with the pp cup by heat sealing, and it is sent to the autoclave for high-pressure sterilization. The sterilization conditions are to continuously increase the temperature to 122 degrees Celsius, maintain 122 degrees Celsius, 2 atmospheres and continue for 30 minutes. Thus, a contact lens having a core body of HEMA as the main component and a water content of about 55% is obtained, and an outer shell layer is mainly composed of PVA-PVAc copolymer and PVP, and the core body of the lens and PVP are connected by PVA-PVAc copolymer. After about 12 hours (including the sterilization process) from the time when the wet lens is in contact with the buffer solution, the aluminum foil is torn off, the contact lens is taken out and placed in a standard buffer solution (Standard buffer) for equilibrium, 10 ml of standard buffer salt is used for one contact lens, and the buffer solution is replaced every 1 hour, and repeated 3 times, and then the surface lubricity of the contact lens is scored.
[0048] Implementation sample 2-2 (EX2-2): Follow the method of implementation sample 2-1, but after the heat-sealing is completed and the aluminum foil and the PP cup are sealed, they are not sent to the autoclave for high-pressure sterilization (autoclave), and the wet lens is only allowed to soak in Buffer-1 in the PP cup with the aluminum foil sealed with heat. After about 12 hours (including the sterilization process) from the time the wet lens contacts the buffer, the aluminum foil is torn off, the corneal contact lens is taken out, and placed in a standard buffer solution (Standard buffer) for balance. One corneal contact lens uses 10 ml of standard buffer salt, and the buffer is replaced every 1 hour. Repeat 3 times, and then the surface lubricity of the corneal contact lens is scored.
[0049] Implementation sample 3-1 (EX3-1): Silicone Hydrogel lens dry film is prepared, and the lens formula is shown in Table 1. The process from lens formula preparation to lens dry film is a well-known technology in the art, and the casting method can be selected for preparation. The curing method of corneal contact lenses can be selected from light curing or thermal curing. In this embodiment, light curing is selected. First, the lens dry film is soaked in an aqueous solution containing 50wt% isopropanol (IPA) for 60 minutes. The purpose is to make the lens dry film expand quickly to increase the cleaning efficiency. At the same time, the principle of high compatibility between IPA and silicon-containing components TRIS and MPDMS is used to ensure that TRIS and MPDMS that have not reacted completely during the curing stage are washed away, and other residual monomers, crosslinking agents, initiators, and diluents are also washed away. Then, it is soaked in RO water at room temperature (20-30 degrees Celsius) for 4 times, each time for 30 minutes, and fresh RO water is replaced each time to ensure that the IPA is cleaned and a lens wet film is obtained. After obtaining the wet lens, the wet lens is immersed in an aqueous solution containing 0.2 g / L of PVA-PVAc copolymer for 120 minutes. The purpose of the immersion process is to allow the PVA-PVAc copolymer to enter the surface layer of the lens core body through mass transfer. The PVA-PVAc copolymer used here is numbered PVA-PVAc-1, which is a PVA-PVAc copolymer with a molecular weight of 31,000 Da and PVA accounting for 88% of the total proportion, that is, a partially hydrolyzed polyvinyl alcohol with a hydrolysis degree of 88%. After completing the above steps, the wet lens is removed from the PVA-PVAc copolymer aqueous solution and placed in a pp cup. Buffer-1 is dripped into the pp cup. The buffer liquid level must be higher than the wet lens to ensure that all the buffer covers the wet lens. After completion, the aluminum foil and the PP cup are sealed by heat sealing, and then sent to the autoclave for high pressure sterilization. The sterilization conditions are to continuously raise the temperature to 122 degrees Celsius, maintain 122 degrees Celsius and 2 atmospheres for 30 minutes. In this way, a contact lens with a core body of silicone hydrogel and an outer shell layer mainly composed of PVA-PVAc copolymer and PVP is obtained, and the core body of the lens and PVP are connected by PVA-PVAc copolymer. About 12 hours (including the sterilization process) after the wet lens contacts the buffer solution, the aluminum foil is torn off, the contact lens is taken out and placed in a standard buffer solution (Standard buffer) for balance. One contact lens uses 10 ml of standard buffer salt, and the buffer solution is replaced every 1 hour. Repeat 3 times, and then the surface lubricity of the contact lens is scored.
[0050] Implementation sample 3-2 (EX3-2): Follow the method of implementation sample 3-1, but after the heat-sealing is completed and the aluminum foil and the PP cup are sealed, they are not sent to the autoclave for high-pressure sterilization (autoclave), and the wet lens is only allowed to soak in Buffer-1 in the PP cup with the aluminum foil sealed. About 12 hours (including the sterilization process) after the wet lens contacts the buffer, the aluminum foil is torn off, the corneal contact lens is taken out, and it is placed in a standard buffer solution (Standard buffer) for balance. One corneal contact lens uses 10 ml of standard buffer salt, and the buffer is replaced every 1 hour. Repeat 3 times, and then the surface lubricity of the corneal contact lens is scored.
[0051] Implementation sample 4-1 (EX4-1): Hydrogel-2 dry lens was prepared. The lens formula is shown in Table 1. The process from preparing the lens formula to preparing the dry lens is a well-known technology in the art. The casting method can be selected for preparation. The curing method of the corneal contact lens can be selected from light curing or heat curing. In this embodiment, light curing is selected. The dry lens was soaked in an aqueous solution containing 0.5wt% sodium carbonate for 20 minutes. The purpose is to allow the MAA in the dry lens to be ionized quickly and expand the dry lens to increase the cleaning efficiency. Then, it was hydrated with RO water at room temperature (20-30 degrees Celsius) for 40 minutes to clean the monomers, crosslinking agents, initiators, and diluents remaining in the dry lens after the curing reaction to obtain a wet lens. After obtaining the wet lens, the wet lens was placed in a pp cup, and buffer-3 (Buffer-3) was dripped into the pp cup. The buffer liquid level must be higher than the wet lens to ensure that all the buffer covers the wet lens. After completion, the aluminum foil and the PP cup are sealed by heat sealing, and then sent to the autoclave for high pressure sterilization (autoclave). The sterilization conditions are to continuously raise the temperature to 122 degrees Celsius, maintain 122 degrees Celsius, 2 atmospheres and continue for 30 minutes. In this way, a contact lens with HEMA as the main component and a water content of about 55% is obtained, and the outer shell layer is mainly composed of PVA-PVAccopolymer and PVP, and the core body of the lens and PVP are connected by PVA-PVAc copolymer. About 12 hours (including the sterilization process) from the beginning of the wet lens contact with the buffer solution, the aluminum foil is torn off, the contact lens is taken out and placed in the standard buffer solution (Standard buffer) for balance. One contact lens uses 10 ml of standard buffer salt, and the buffer is replaced every 1 hour. Repeat 3 times, and then the surface lubricity of the contact lens is scored. The ratio of Buffer-3 is recorded in Table 2.
[0052] Implementation sample 4-2 (EX4-2): Hydrogel-2 lens dry film was prepared, and the lens formula is shown in Table 1. The process from lens formula preparation to lens dry film is a well-known technology in the art, and the casting method can be selected for preparation. The curing method of corneal contact lenses can be selected from light curing or heat curing. In this embodiment, light curing is selected. The lens dry film is soaked in an aqueous solution containing 0.5wt% sodium carbonate for 20 minutes, the purpose is to allow the MAA in the lens dry film to be quickly ionized, so that the lens dry film can expand to increase the cleaning efficiency, and then hydrated with RO water at room temperature (20-30 degrees Celsius) for 40 minutes, and the monomers, cross-linking agents, initiators, and diluents remaining in the lens dry film after the curing reaction are washed off to obtain a lens wet film. After obtaining the lens wet film, the lens wet film is soaked in an aqueous solution containing 0.6g / L PVP for 120 minutes. The purpose of this soaking process is to allow PVP to enter the surface layer of the lens core body through mass transfer. The PVP number used here is PVP360, which is a PVP with a molecular weight of 360,000Da. After completing the above steps, the wet lens is removed from the PVP aqueous solution and placed in a pp cup. Buffer-2 is dripped into the pp cup. The buffer liquid level must be higher than the wet lens to ensure that all the buffer covers the wet lens. After completion, the aluminum foil and the pp cup are sealed by heat sealing, and sent to the autoclave for high pressure sterilization. The sterilization conditions are to continuously increase the temperature to 122 degrees Celsius, maintain 122 degrees Celsius, 2 atmospheres and continue for 30 minutes. About 12 hours (including the sterilization process) from the time the wet lens contacts the buffer, the aluminum foil is torn off, the corneal contact lens is taken out and placed in a standard buffer solution (Standard buffer) for balance. One corneal contact lens uses 10ml of standard buffer salt, and the buffer is changed every 1 hour. Repeat 3 times, and then the surface lubricity of the corneal contact lens is scored. The ratio of Buffer-2 is recorded in Table 2.
[0053] Implementation sample 5-1 (EX5-1): The same method as implementation sample 4-1 was followed, but the PVP in the buffer was replaced with Copolymer 845. About 12 hours (including the sterilization process) after the wet lens was in contact with the buffer, the aluminum foil was torn off, the contact lens was taken out, and placed in a standard buffer solution (Standard buffer) for equilibrium. One contact lens used 10 ml of standard buffer solution, and the buffer was replaced every 1 hour, and this was repeated 3 times. After that, the surface lubricity of the contact lens was scored.
[0054] Implementation sample 5-2 (EX5-2): Hydrogel-2 dry lens was prepared. The lens formula is shown in Table 1. The process from preparing the lens formula to preparing the dry lens is a well-known technology in the art. The casting method can be selected for preparation. The curing method of the corneal contact lens can be selected from light curing or heat curing. In this embodiment, light curing is selected. The dry lens was soaked in an aqueous solution containing 0.5wt% sodium carbonate for 20 minutes. The purpose is to allow the MAA in the dry lens to be ionized quickly and expand the dry lens to increase the cleaning efficiency. Then, it was hydrated with RO water at room temperature (20-30 degrees Celsius) for 40 minutes to wash away the monomers, crosslinking agents, initiators, and diluents remaining in the dry lens after the curing reaction to obtain a wet lens. After obtaining the wet lens, the wet lens was placed in a pp cup, and buffer-2 was dripped into the pp cup. The buffer liquid level must be higher than the wet lens to ensure that all the buffer covers the wet lens. After completion, the aluminum foil and the PP cup are sealed by heat sealing, and then sent to the autoclave for high pressure sterilization (autoclave). The sterilization conditions are to continue to heat up to 122 degrees Celsius, maintain 122 degrees Celsius, 2 atmospheres and continue for 30 minutes. After the above sterilization is completed, the aluminum foil is torn off, the corneal contact lens is taken out and placed in another new PP cup, and buffer-1 is dripped into the PP cup. The buffer liquid level must be higher than the wet lens to ensure that all the buffer covers the wet lens. After completion, the aluminum foil and the PP cup are sealed by heat sealing, and then sent to the autoclave for the second high pressure sterilization (autoclave). The sterilization conditions are to continue to heat up to 122 degrees Celsius, maintain 122 degrees Celsius, 2 atmospheres and continue for 30 minutes. After completion, the aluminum foil was torn off, and the contact lens was taken out and placed in a standard buffered saline solution (Standard buffer) for equilibrium. 10 ml of standard buffered saline was used for one contact lens, and the buffer was replaced every 1 hour. This was repeated 3 times, and then the surface lubricity of the contact lens was scored.
[0055] Implementation sample 6-1 (EX6-1): The preparation method of implementation sample 4-1 was followed, but the buffer was replaced with buffer-4. The ratio of Buffer-4 is recorded in Table 2. After sterilization, it was confirmed that about 12 hours (including the sterilization process) had passed since the wet lens contacted the buffer. The aluminum foil was torn off, and the contact lens was taken out and placed in a standard buffer solution (Standard buffer) for equilibrium. One contact lens used 10 ml of standard buffer, and the buffer was replaced every 1 hour. This was repeated 3 times, and then the surface lubricity of the contact lens was scored.
[0056] Implementation sample 7-1 (EX7-1): The preparation method of implementation sample 4-1 was followed, but buffer-3 was replaced with buffer-5 (Buffer-5), and the ratio of Buffer-5 was recorded in Table 2. After sterilization, it was confirmed that about 12 hours (including the sterilization process) had passed since the wet lens contacted the buffer, the aluminum foil was torn off, the contact lens was taken out and placed in a standard buffer solution (Standard buffer) for equilibrium, 10 ml of standard buffer was used for one contact lens, and the buffer was replaced every 1 hour, and repeated 3 times, and then the surface lubricity of the contact lens was scored.
[0057] Implementation sample 8-1 (EX8-1): The preparation method of implementation sample 4-1 was followed, but buffer-3 was replaced with buffer-6 (Buffer-6), and the ratio of Buffer-6 was recorded in Table 2. After sterilization, it was confirmed that about 12 hours (including the sterilization process) had elapsed since the wet lens contacted the buffer, the aluminum foil was torn off, the contact lens was taken out and placed in a standard buffer solution (Standard buffer) for equilibrium, 10 ml of standard buffer was used for each contact lens, and the buffer was replaced every 1 hour, and repeated 3 times, and then the surface lubricity of the contact lens was scored.
[0058] Implementation sample 9-1 (EX9-1): Hydrogel-2 lens dry film was prepared, and the lens formula is shown in Table 1. The process from lens formula preparation to lens dry film is a well-known technology in the art, and the casting method can be selected for preparation. The curing method of corneal contact lenses can be selected from light curing or thermal curing. In this embodiment, light curing is selected. The lens dry film was soaked in an aqueous solution containing 0.5wt% sodium carbonate for 20 minutes, in order to allow the MAA in the lens dry film to be ionized quickly and expand the lens dry film to increase the cleaning efficiency. Then, it was hydrated with RO water at room temperature (20-30 degrees Celsius) for 40 minutes, and the monomers, crosslinking agents, initiators, and diluents remaining in the lens dry film after the curing reaction were washed off to obtain a lens wet film. After obtaining the wet lens, the wet lens is immersed in an aqueous solution containing 0.2 g / L PVA (molecular weight 145,000 Da, hydrolysis degree 99%) and heated at 70 ± 5 degrees Celsius for 120 minutes. Then, the wet lens is immersed in an aqueous solution containing 0.6 g / L PVP (molecular weight 360,000 Da) and heated at 70 ± 5 degrees Celsius for 120 minutes. After obtaining the wet lens, the wet lens is placed in a pp cup, and the standard buffer salt solution is dripped into the pp cup. The buffer solution liquid level must be higher than the wet lens to ensure that all the buffer solution covers the wet lens. After completion, the aluminum foil is sealed with the pp cup by heat sealing, and it is sent to the autoclave for high pressure sterilization. The sterilization conditions are to continuously increase the temperature to 122 degrees Celsius, maintain 122 degrees Celsius, 2 atmospheres and continue for 30 minutes. About 12 hours after the wet lens contacted the buffer solution (including the sterilization process), the aluminum foil was torn off, and the contact lens was taken out and placed in the standard buffer solution (Standard buffer) for equilibrium. 10 ml of standard buffer salt was used for each contact lens, and the buffer solution was changed every 1 hour. This was repeated 3 times, and then the surface lubricity of the contact lens was scored. The proportion of the standard buffer solution is recorded in Table 2.
[0059] Implementation sample 6-2 (EX6-2): The preparation method of implementation sample 9-1 was imitated, but after the aluminum foil and the PP cup were sealed by heat sealing, they were not sent to the autoclave for high pressure sterilization (autoclave), and the wet lens was only allowed to soak in the PP cup with the aluminum foil sealed by heat sealing and the standard buffered saline solution. About 12 hours (including the sterilization process) after the wet lens contacted the buffer solution, the aluminum foil was torn off, the corneal contact lens was taken out, and it was placed in the standard buffered saline solution (Standard buffer) for balance. 10 ml of standard buffered salt was used for one corneal contact lens, and the buffer was changed every 1 hour, and repeated 3 times, and then the surface lubricity of the corneal contact lens was scored.
[0060] Implementation sample 7-2 (EX7-2): The preparation method of implementation sample 4-1 was followed, but buffer-3 was replaced with buffer-1 (Buffer-1), and the ratio of Buffer-1 was recorded in Table 2. After sterilization, it was confirmed that about 12 hours (including the sterilization process) had elapsed since the wet lens contacted the buffer, the aluminum foil was torn off, the contact lens was taken out and placed in a standard buffer solution (Standard buffer) for equilibrium, 10 ml of standard buffer was used for each contact lens, and the buffer was replaced every 1 hour, and repeated 3 times, and then the surface lubricity of the contact lens was scored.
[0061] Implementation of Sample 8-2 (EX8-2): The implementation of Sample 7-2 was similar to that of Sample 7-2, but before evaluating the surface lubricity of the contact lens, the aluminum foil was torn off, and the contact lens was taken out and placed in a standard buffered saline solution (Standard buffer) for equilibrium. 10 ml of standard buffered saline was used for each contact lens, and the buffer solution was replaced every hour. This was repeated three times before the surface lubricity of the contact lens was scored.
[0062] Implementation sample 9-2 (EX9-2): The preparation method of implementation sample 4-1 was followed, but buffer-3 was replaced with buffer-2 (Buffer-2), and the ratio of Buffer-2 was recorded in Table 2. After sterilization, it was confirmed that about 12 hours (including the sterilization process) had elapsed since the wet lens contacted the buffer, the aluminum foil was torn off, the contact lens was taken out and placed in a standard buffer solution (Standard buffer) for equilibrium, 10 ml of standard buffer was used for each contact lens, and the buffer was replaced every 1 hour, and repeated 3 times, and then the surface lubricity of the contact lens was scored.
[0063] Surface lubricity score of contact lenses. The surface lubricity of contact lenses is divided into 1-4 points, and the higher the score, the higher the lubricity of the contact lenses. 1 point means that the contact lenses feel completely unlubricated when rubbed with fingers. 2 points means that the contact lenses feel a little lubricated when rubbed with fingers, which is equivalent to the commercially available contact lens product Acuvue Oasys 1day in terms of score. 3 points means that the contact lenses have a moderate lubricity. 4 points means that the contact lenses are very lubricated, which is equivalent to the commercially available contact lens product Dailies Total 1 in terms of score. It must be noted that some users who wear contact lenses evaluate that Dailies Total 1 feels very good to wear, but because the contact lenses are too slippery, it is very difficult to remove the contact lenses from the eyes after use, affecting the user's willingness to continue using this brand of contact lenses. Therefore, the higher the lubricity of the contact lenses, the better. The most suitable lubricity in the evaluation of the present invention is 3 points.
[0064] Surface lubricity scoring test method: 5 testers are selected, and each tester will rub the two products, Acuvue Oasys1day and Dailies Total 1, and the lubricity of the rubbing feeling of Acuvue Oasys 1day is calibrated as 2 points, and the lubricity of the rubbing feeling of Dailies Total 1 is calibrated as 4 points. If 4 of the 5 testers think that the lubricity of the test sample is significantly lower than Acuvue Oasys 1day, the lubricity score of the test sample will be recorded as 1 point. If only 3 testers think that the lubricity of the test sample is lower than Acuvue Oasys 1day, and 2 testers think that the difference with Acuvue Oasys 1day is not significant, it will be recorded as 1-2 points. If more than 4 testers think that the lubricity of the test sample is equivalent to Acuvue Oasys 1day, it will be recorded as 2 points. If more than 3 testers think that the lubricity of the test sample is significantly higher than Acuvue Oasys 1day, and the other 2 testers think that the lubricity of the test sample is equivalent to Acuvue Oasys 1day, it will be recorded as 2-3. If more than 4 respondents thought that the lubricity was significantly higher than Acuvue Oasys 1day, it was recorded as 3 points.
[0065] The surface lubricity scores of the samples implemented in this study are shown in Table 3.
[0066] Table 3
[0067]
[0068]
[0069] It can be seen from the data in Table 3 that according to the technical solution proposed in the present invention (implementation samples EX1-1, 2-1, 3-1, 4-1, 5-1, 6-1, 7-1, 8-1 and 9-1), the surface lubricity can be effectively improved and the surface lubricity can be controlled within an appropriate range. The main difference between implementation sample 1-1 (EX1-1) and implementation sample 1-2 (EX1-2) is whether sterilization is performed. Implementation sample 1-1 that has been sterilized has a higher surface lubricity, with a score of 3 points. Similarly, the surface lubricity score of implementation sample 2-1 (EX2-1) is also higher than that of implementation sample 2-2 (EX2-2). The surface lubricity score of implementation sample 3-1 (EX3-1) is also higher than that of implementation sample 3-2 (EX3-2), and the reason is similar to that of implementation sample 1-1 (EX1-1), which will not be repeated here. Implementation sample 4-1 (EX4-1) is similar to implementation sample 4-2 (EX4-2), and the main difference between the two is that the timing of contacting the first polymer and the second polymer with the lens core body is different. In implementation sample 4-1 (EX4-1), the lens core body is immersed in a buffer containing both the first polymer and the second polymer, so that the first polymer can effectively form an interpenetrating polymer network structure with the surface structure of the lens core body, thereby affecting the surface lubricity of the final corneal contact lens. The main difference between implementation sample 5-1 (EX5-1) and implementation sample 5-2 (EX5-2) is that implementation sample 5-2 is sterilized twice, the first sterilization is performed after immersion in buffer-2 containing PVA, and the second sterilization is performed after immersion in buffer-1 containing PVP. From the surface lubricity score, it can be seen that the score of implementation sample 5-1 is higher than that of implementation sample 5-2. The reason may be that during the first sterilization of sample 5-2, some polyvinyl alcohol in the first polymer formed strong hydrogen bonds and cross-linking reactions, which hindered the second polymer from forming an outer shell with the first polymer during the second sterilization, which may make the outer shell less stable, resulting in a lower surface lubricity score. Compared with sample 6-2 (EX6-2), sample 9-1 (EX9-1) has a higher surface lubricity score because it has been sterilized. Sample 4-1 (EX4-1) is similar to sample 7-2 (EX7-2), and the main difference is that the buffer-3 in which sample 4-1 is immersed contains not only the second polymer but also the first polymer, so that the second polymer can be stably present on the surface of the lens core body with the help of the first polymer, so the surface lubricity score of sample 4-1 is higher. Similarly, the surface lubricity score of sample 4-1 (EX4-1) is higher than that of sample 8-2 (EX8-2), which will not be repeated here.Compared with implementation sample 9-2 (EX9-2), implementation sample 4-1 (EX4-1) has a higher surface lubricity score than implementation sample 9-2 because the buffer-3 in which implementation sample 4-1 is immersed contains not only the first polymer but also the second polymer, which helps to form a shell layer that increases the surface lubricity of the corneal contact lens.
[0070] The contact lenses of implementation samples 4-1 and 7-2 were rinsed with RO water for 3 times to remove the components on the surface of the contact lenses that can be removed by RO water (including buffer salts NaCl, NaH2PO4, Na2HPO4), and then the contact lenses were dried at 105°C for at least 8 hours to remove the moisture from the contact lenses to obtain dry lenses, and the surface components of the dry lenses were analyzed by the elemental analysis function of a scanning electron microscope (Energy-dispersive X-ray spectroscopy with Scanning Electron Microscope, SEM-EDX). The elemental analysis data showed that the surface of the dry lens treated with implementation sample 4-1 had 4.39% nitrogen, indicating that even after RO water rinsing, the second polymer (PVP) still existed stably on the surface of the lens core body. However, no nitrogen could be detected on the surface of the dry lens treated with implementation sample 7-2, indicating that after RO water rinsing, the second polymer (PVP) originally on the surface of the lens core body had been washed away. Therefore, the SEM-EDX analysis method can further illustrate that the core body of the corneal contact lens of one embodiment of the present invention is coated by the outer shell layer containing the second polymer (PVP).
[0071] From the above data analysis and explanation, it can be confirmed that the technical solution proposed by the present invention can effectively make the corneal contact lens have a moderate surface lubricity, which is beneficial to increase the comfort of wearing the corneal contact lens.
[0072] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes by using the methods and technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A corneal contact lens, characterized in that: The invention comprises a lens core body and a shell layer, wherein the shell layer covers the lens core body; wherein the shell layer comprises a first polymer and a second polymer, wherein the first polymer comprises polyvinyl alcohol, and the second polymer comprises polyvinyl pyrrolidone.
2. The contact lens according to claim 1, wherein: The first polymer covers the lens core body, and the second polymer covers the first polymer.
3. The contact lens according to claim 1, wherein: The first polymer is partially hydrolyzed polyvinyl alcohol with a hydrolysis degree of 70% to 99%.
4. The contact lens according to claim 1, wherein: The first polymer is partially hydrolyzed polyvinyl alcohol with a hydrolysis degree of 80% to 98%.
5. The contact lens according to claim 1, wherein: The first polymer is partially hydrolyzed polyvinyl alcohol with a hydrolysis degree of 88% to 95%.
6. The contact lens according to claim 1, wherein: The molecular weight of the second polymer is greater than or equal to 8,000 Da.
7. The contact lens according to claim 1, wherein: The molecular weight of the second polymer is greater than or equal to 160,000 Da.
8. The contact lens according to claim 1, wherein: The molecular weight of the second polymer is greater than or equal to 360,000 Da.
9. The contact lens according to claim 1, wherein: The second polymer further includes dimethylaminoethyl methacrylate.
10. The contact lens according to claim 9, wherein: The molecular weight of the second polymer is greater than or equal to 100,000 Da.
11. The contact lens according to claim 1, wherein: The corneal contact lens is a hydrogel corneal contact lens.
12. The contact lens according to claim 1, wherein: The corneal contact lens is a silicone hydrogel corneal contact lens.
13. A corneal contact lens, characterized in that: The lens comprises a lens core body and a shell layer, wherein the shell layer covers the lens core body; wherein the shell layer comprises a first polymer and a second polymer, wherein the first polymer comprises polyvinyl alcohol, and the second polymer comprises polyvinyl pyrrolidone; The elemental analysis of the corneal contact lens using a scanning electron microscope can detect nitrogen, and the nitrogen comes from the outer shell layer.
Citation Information
Cited By
Moisture gradient silicone hydrogel contact lenses
JP2026504351A